The intrinsic fallacy of market mechanism and private property rights in alleviating the tragedy of the commons - Cebeci, Ali Fehim; Ince, Huseyin; Mercan, Murat Anil (Routledge Journals, Taylor & Francis Ltd, 2020)
Economists' solution to the tragedy of the commons relies on well-defined property rights and competitive market mechanism for limiting individuals' self-serving, short-sighted actions that result in a dramatic depletion of the common resources. However, this solution implicates a serious threat in terms of sustainability. Recently, deterioration of genetic diversity reached alarming levels, mainly attributed to escalating economic pressure that obliges farmers to shift from local breeds towards more profitable and more productive industrial breeds. This study empirically examines the efficiency of the free market mechanism as a solution to the tragedy of the commons through a unique natural experiment in which a huge demand shock arises regarding sheep. Results robustly show that the free market mechanism can cope with even a very challenging demand shock through the adjustment of prices without any shortage of the commodity. However, this finding does not guarantee that such an outcome is sustainable over the very long term. Analysis of the growth rate of the local sheep breeds population and cross-breed sheep population shows that the trend is overwhelmingly in favour of cross-breeds, thus supporting concerns for a free market mechanism, intrinsically driving the extinction of local sheep breeds, an invaluable genetic resource.
Keywords: Excess demand; price adjustment; sustainability; genetic diversity